Do Working Capital Efficiency and Capital Structure Shape Financial Distress? The Moderating Role of Firm Size in Food and Beverage Firms Listed on the Indonesia Stock Exchange - Aditya Rahmadani; Solikah Nurwati; Putri Salasyah Riadin Nengsih; Novia Safitri (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines Cash Conversion Cycle (CCC) and Debt to Equity Ratio (DER) as determinants of financial distress, with firm size tested as a moderating variable, among Food and Beverage companies on the IDX during 2021–2025. Financial distress is operationalized through the Altman Emerging Market Score (EMS), estimated via a Fixed Effect Model with clustered standard errors using panel data from 63 companies yielding 315 observations. Rising CCC is found to significantly worsen financial distress, while DER exhibits a similar but statistically weak tendency. Firm size fails to moderate either relationship. Substituting Debt to Asset Ratio as an alternative leverage proxy confirms that asset-based leverage significantly deteriorates financial distress, reinforcing the robustness of the main findings.